Pengembangan Model Blended Learning Berbasis Google Classroom Pada Mata Kuliah Rekayasa Sistem Audio - Supriadi Supriadi; Mahmud Mustafa (Seminar Nasional LP2M UNM, 2019)
Abstract. The purpose of this study was to determine the development and feasibility of a google classroom-based Blended Learning model in the Audio System Engineering course in the Department of Electronics Engineering FT-UNM. This research is a research and development of Research and Dependency (R&D). According to Punaji Setyosari (2010: 230), states that research development is a process used to develop and validate educational products. The development of the Google classroom-based blended learning model follows the stages of the development of an educational design model from Plomp. Plomp shows that a model in designing education (including learning) consists of 5 (five) stages, namely the initial investigation stage, the design / design stage, the realization / construction stage, the test phase, evaluation and revision & implementation stage. Based on these steps, then combined with the elements of the development of learning models proposed by Joyce & Weil, the model of developing learning material (products) by Nieveen, and the instructional system development model by Dick & Carey. The feasibility of a google classroom-based blended learning model in the Audio System Engineering course that has been developed is declared "Very Eligible" based on the results of the model validation carried out by experts by covering aspects of model content, model instructions and language in the Department of Electronic Engineering FT-UNM. Keywords: Blended, learning, google, classroom